Synthetic DNA and RNA Programming - O'Donoghue, Patrick (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Dear Colleagues, Synthetic biology is a broad and emerging discipline that capitalizes on recent advances in molecular biology, genetics, protein and RNA engineering and omics technologies. These technologies have transformed our ability to reveal the biology of the cell and the molecular basis of disease.